Pollution Level Reduction of Tofu Waste Water in Nata de Soya Production (Incubation Time Study) - Nisa, Fithri Choirun (Jurnal Teknologi Pertanian, 2002)
The waste from pre and post harvesting may cause environmental problem. This problem need to be solved. The waste water (whey) from tofu production is one of that always be produced in large amount. The objective of this research was to use whey of tofu to produce nata de soya and to reduce environmental pollution by varying incubation time. Total nitrogen, reducing sugar, COD value, and pH were analyzed in initial whey of tofu. Thickness and weight of nata that produced, volume and COD (Chemical Oxygen Demand) value of whey residue were observed after 10, 12, 14, 16, and 18 days. The optimum incubation time for nata production was 14 days with the thickness and the wet weight of nata that produced are 4,75 mm and 24,58 g, respectively and COD reduction 46,22%. These results were derived from 200 ml whey that enriched by sucrose 10% (w/v) and mungbean sprout extract 0,5% (v/v) Â  Keywords: tofu wastewater, nata de soya, incubation, pollution reduction